Antimicrobial Activity of Cinnamaldehyde on Streptococcus mutans Biofilms - He, Zhiyan; Huang, Zhengwei; Jiang, Wei; Zhou, Wei (Frontiers in Microbiology, 2019)
Streptococcus mutans is considered the most relevant bacteria in the transition of non-pathogenic commensal oral microbiota to biofilms which contribute to the dental caries process. The present study aimed to evaluate the antimicrobial activity of a natural plant product, cinnamaldehyde against S.mutans biofilms. Minimum inhibitory concentrations (MIC), minimal bactericidal concentration (MBC), and growth curves were determined to assess its antimicrobial effect against planktonic S. mutans. The biofilm biomass and metabolism with different concentrations of cinnamaldehyde and different incubation time points were assessed using the crystal violet and MTT assays. The biofilms were visualized using confocal laser scanning microscopy (CLSM). Bacterial cell surface hydrophobicity, aggregation, acid production, and acid tolerance were evaluated after cinnamaldehyde treatment. The gene expression of virulence-related factors (gtfB, gtfC, gtfD, gbpB, comDE, vicR, ciaH, ldh and relA) was investigated by real-time PCR. The MIC and MBC of cinnamaldehyde against planktonic S. mutans were 1000 and 2000 μg/mL, respectively. The results showed that cinnamaldehyde can decrease biofilm biomass and metabolism at sub-MIC concentrations. CLSM images revealed that the biofilm-covered surface areas decrease with increasing concentrations of cinnamaldehyde. Cinnamaldehyde increased cell surface hydrophobicity, reduced S. mutans aggregation, inhibited acid production, and acid tolerance. Genes expressions in the biofilms were down-regulated in the presence of cinnamaldehyde. Therefore, our data demonstrated that cinnamaldehyde at sub-MIC level suppressed the microbial activity on S. mutans biofilm by modulating hydrophobicity, aggregation, acid production, acid tolerance, and virulence gene expression.